Progress in anterior chamber angle imaging for glaucoma risk prediction – A review on clinical equipment, practice and research. Issue 12 (December 2016) - V.K., Shinoj; Hong, Xun Jie Jeesmond; V.M., Murukeshan; M., Baskaran; Tin, Aung
Highlights: Thrust research and developmental works in the forefront of innovation. Anterior chamber imaging techniques in glaucoma diagnosis and follow-up procedures. Critical analysis of existing photographic and tomographic optical imaging methods. Abstract: The visualization capabilities of various ocular imaging instruments can generally be categorized into photographic (e.g. gonioscopy, Pentacam, RetCam) and optical tomographic (e.g. optical coherence tomography (OCT), photoacoustic (PA) imaging, ultrasound biomicriscopy (UBM)) methods. These imaging instruments allow vision researchers and clinicians to visualize the iridocorneal angle, and are essential in the diagnosis and management of glaucoma. Each of these imaging modalities has particular benefits and associated drawbacks in obtaining repeatable and reliable measurement in the evaluation of the angle. This review article in this context summarized recent progresses in anterior chamber imaging techniques in glaucoma diagnosis and follow-up procedures.